2021
DOI: 10.3390/met11030385
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pre-Aging on the Artificial Aging Behavior of a 6056 Aluminum Alloy after Conventional Extrusion

Abstract: In the present study, the influence of the initial heat-treatment conditions on the artificial aging behavior after conventional linear extrusion at room temperature was investigated for the precipitation hardening of a 6056 aluminum alloy. A solution-annealed condition was systematically compared to naturally-aged and pre-aged conditions. Differential scanning calorimetry was used for analyzing the precipitation sequence and its dependence on the initial heat treatment. The natural aging behavior prior to ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
6
0
1
Order By: Relevance
“…H. Jiang et al [33] reported that high-density dispersed precipitation of the η'-phase, the main reinforcing phase of AA7055 alloy, was improved through pre-aging and, X. Liao et al [34] reported that the main reinforcing phase, the η'-phase, was formed more finely with a higher volume fraction through the application of pre-aging to Al-Zn-Mg-Cu alloys. Also, L. Winter et al [35] reported that by applying pre-aging to AA6056 alloy, the formation of room-temperature clusters and natural aging were suppressed after solid solution treatment, and the artificial aging reactivity was greatly improved. It was confirmed that pre-aging was advantageous to the mechanical properties of the designed alloy based on the size of the precipitate phases that were maintained at a smaller size through pre-aging and the number density of the precipitate phases per unit area.…”
Section: Phase Analysismentioning
confidence: 99%
“…H. Jiang et al [33] reported that high-density dispersed precipitation of the η'-phase, the main reinforcing phase of AA7055 alloy, was improved through pre-aging and, X. Liao et al [34] reported that the main reinforcing phase, the η'-phase, was formed more finely with a higher volume fraction through the application of pre-aging to Al-Zn-Mg-Cu alloys. Also, L. Winter et al [35] reported that by applying pre-aging to AA6056 alloy, the formation of room-temperature clusters and natural aging were suppressed after solid solution treatment, and the artificial aging reactivity was greatly improved. It was confirmed that pre-aging was advantageous to the mechanical properties of the designed alloy based on the size of the precipitate phases that were maintained at a smaller size through pre-aging and the number density of the precipitate phases per unit area.…”
Section: Phase Analysismentioning
confidence: 99%
“…During the subsequent heating (e.g., prior to hot compression testing), these (caused by the low cooling rate) sparsely distributed precipitates grow while their coherency decreases. However, it can be assumed that the precipitation kinetic during testing at 350 • C of the as-sintered conditions starts with the formation of GP I zones at about 190 • C, see Figure 5 (I), which indicates that Si-, Mg-and Mg-Si co-clusters were already present after sintering [9]. This peak is followed by the overlapping formation of β ′′ (III), β' (IV) and β (V) precipitates, from about 240 • C to 380 • C. At about 380 • C, the precipitation ends and the dissolution of the Mg 2 Si phases begins for both conditions.…”
Section: Compressive Behavior At 350 • Cmentioning
confidence: 99%
“…In addition, the presence of the alloying elements Si and Mg allows for a significant improvement in strength due to precipitation hardening. The precipitation sequence is generally accepted as [7][8][9]: super saturated solid solution → clusters → Guinier-Preston zones (GP I, coherent) → β ′′ (semi-coherent, needle-shaped) → β ′ (semi-coherent, rod-shaped) → β (incoherent). The highest strength can be achieved by a T6 heat treatment routine, i.e., solution annealing, water quenching and artificial ageing at elevated temperatures to achieve a high amount of finely dispersed β ′′ precipitates.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al [14] found that aging time had a significant impact on the anti-corrosion resistance of the 6061-T6 aluminum alloy due to the content of the β phase. Winter et al [15] reported that pre-aging enhanced the effect of artificial aging on the hardness and strength of the 6056 aluminum alloy.…”
Section: Introductionmentioning
confidence: 99%